Existence and global attractivity positive periodic solutions for a discrete model - Zheng Zhou; Zhengqiu Zhang (Electronic Journal of Differential Equations, 2006)
Using a fixed point theorem in cones, we obtain conditions that guarantee the existence and attractivity of the unique positive periodic solution for a discrete Lasota-Wazewska model.